2021
DOI: 10.1002/ehf2.13296
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent heart failure hospitalizations increase the risk of cardiovascular and all‐cause mortality in patients with heart failure in Sweden: a real‐world study

Abstract: Aims Heart failure (HF) is a leading cause of hospitalization and is associated with high morbidity and mortality. We examined the impact of recurrent HF hospitalizations (HFHs) on cardiovascular (CV) mortality among patients with HF in Sweden. Methods and results Adults with incident HF were identified from linked national health registers and electronic medical records from 01 January 2005 to 31 December 2013 for Uppsala and until 31 December 2014 for Västerbotten. CV mortality and all-cause mortality were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This finding is considered consistent when compared with a previous HF registry study. 27 However, other similar studies have shown mortality to be as low as 8.2%. 14 31 The difference is attributed to the fact that mortality in the present study is calculated from the first day of HF diagnosis, whereas comparable HF registry studies do not take the date of diagnosis into consideration.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is considered consistent when compared with a previous HF registry study. 27 However, other similar studies have shown mortality to be as low as 8.2%. 14 31 The difference is attributed to the fact that mortality in the present study is calculated from the first day of HF diagnosis, whereas comparable HF registry studies do not take the date of diagnosis into consideration.…”
Section: Discussionmentioning
confidence: 92%
“…There is a strong association between recurrent HFH and cardiovascular (CV) and all-cause mortality, with the risk increasing progressively with each recurrent HFH. 5 This increases the burden on the patient and the healthcare system.…”
Section: Impact Of Hf Hospitalization On Mortalitymentioning
confidence: 99%
“…The number of HF hospitalizations is a strong predictor of cardiovascular (CV) and all-cause mortality [ 8 , 9 ].…”
Section: Do Patients With Advanced Heart Failure (Hf) Have a Need For...mentioning
confidence: 99%